Structural behaviour of a single tendon end block - Nuid, Maria (2010)
There are many proprietry design for end blocks with cable of multiple tendons available in the market. However, in this study tests have been carried out on end block with single tendon specifically design for laboratory work. This study investigate the effect of different types of bursting reinforcement, number of bearing plate and size of end block for a single tendon cable. A total number of 18 end blocks have been tested until failure using a compression testing machine. Failure load were than compared with those obtained from design using BS 8110: 1997 and CIRIA guide 1 (1976). Test results show that spiral bursting reinforcement failed with higher failure load than orthogonal bursting reinforcement. Is has been noticed that end block using two bearing plate separately can accommodate a higher failure load compared with using only a single bearing plate. The overall failure loads for all the specimens are closer to that design by BS 8110: 1997 and thus it can be concluded that it is a more conservative design than CIRIA guide 1 (1976).